AN ANALYSIS OF THE FACTORS AFFECTING DEINDUSTRIALIZATION IN FOUR COUNTRIES - Muhammad Rizki Taufik; I Nyoman Wahyu Widiana (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
The phenomenon of premature deindustrialization is increasingly prevalent in developing countries, where the manufacturing sector experiences a decline in its contribution to GDP before reaching the stage of industrial maturity. Indonesia, India, Colombia, and South Africa are examples of countries that have shown this tendency in recent decades. This study aims to analyze the simultaneous and partial effects of Gross Domestic Product (GDP) per capita, exchange rate, and trade openness on deindustrialization in these four countries during the period 1995–2023. This research utilizes secondary data obtained from the World Bank and applies panel data regression analysis. The Chow and Hausman tests indicate that the most appropriate model to use is the Fixed Effect Model (FEM). The results reveal that, simultaneously, the three independent variables have a significant effect on the contribution of the manufacturing sector. Partially, GDP per capita and exchange rate have a negative and significant effect, while trade openness has a positive and significant effect on the contribution of the manufacturing sector. These findings highlight the need for adaptive industrial development policies, particularly in maintaining exchange rate stability and promoting open trade that can enhance the competitiveness of the manufacturing sector in these four countries.